Is sports science answering the call for interdisciplinary research? A systematic review - Piggott, B.; Müller, S.; Chivers, P.; Papaluca, C.; Hoyne, G. (European Journal of Sport Science, 2019)
Sports science research is traditionally monodisciplinary despite calls for an interdisciplinary focus. The primary purpose of this systematic review was to identify studies on talent identification, talent selection and competition performance to determine whether interdisciplinary research is being conducted. Thirty-six studies met the selection criteria. These studies were critiqued relative to sport, skill level, sport science sub-disciplines included, and whether the research was multidisciplinary or interdisciplinary. The secondary purpose of the review was to critique the level of analysis and level of representative task design in performance tests used in the studies. Twenty-five studies were categorised as interdisciplinary, with 11 categorised as multidisciplinary. Thirteen sports were represented with soccer the most frequent followed by field hockey, Australian Rules football, handball and rugby league. Thirty-two studies completed their analysis at a group level and four at an individual level. A total of 337 performance tests were rated for representative task design with 64 categorised as low, 123 as medium and 150 as high. The results pertaining to interdisciplinary studies and individual analyses are discussed in relation to constraints theory, which predicts that interacting variables can explain sport performance. Sports science research is beginning to fulfil the call for interdisciplinary research. Future research, however, needs to consider individual analyses and representative task design of tests to progress sports science knowledge.